Julia [videorecording (DVD)] - Fonda, Jane, 1937-; Redgrave, Vanessa, 1937-; Robards, Jason; Holbrook, Hal; Schell, Maximilian; Hellman, Lillian, 1905-1984 (20th Century Fox Home Entertainment, 2005)
Born to great wealth, the fiercely independent Julia devotes her life to political causes, fighting fascism in the 1930's. While traveling in Europe, playwright Lillian Hellman, a friend of Julia's, is swept into a dangerous world, smuggling money across hostile borders.